PROSPEKTIF KEBIJAKAN KEPEMILIKAN HAK ATAS TANAH BAGI WARGANEGARA ASING DI INDONESIA - Widyarini Indriasti W (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2014)
The regulation of land ownership had already existed and stipulated in the UUPA. Article 42 of UUPA regulate the land ownership stipulation for foreigners, i.e. foreigners can only have use rights and leasehold. Government Regulation No. 41 of 1996 stipulates that the use rights for foreigners may occur on State Land, Properties Land and land management rights. The regulation of land rights for foreigners in Indonesia stipulated in Government Regulation No.41 of 1996 on Live Home or Residential Ownership by Foreigners domiciled in Indonesia. Law No. 1 of 2011 on Housing and Settlement Zone, which in Article 52 stipulated that foreigners could inhabit or occupy the home by rights of leases or rights of use. Government Regulation No. 41 of 1996 intended to provide the possibility of legal certainty for foreigners to have a house or dwelling which is located in Indonesia, however, the implementation has not been able to provide a clear legal for foreign citizen in related with property investment in Indonesia, as well as the emergence of smuggling law of land by foreigners which cannot be handled due to the lack of oversight and follow-up sanctions.